Tinjauan Yuridis terhadap Putusan Pengadilan Negeri terkait dengan Kompetensi Absolut dalam Penyelesaian Sengketa Perbankan Syariah - Sugiannur Sugiannur; Wahda Z Imam; Nam Rumkel (Faculty of Law, Khairun University, 2020)
Article 18 of Law Number 48 of 2009 concerning Judicial Power determines that judicial power is exercised by a Supreme Court and judicial bodies under it in the general court, religious courts, military courts, state administrative courts, and by an Constitutional Court. Each judicial environment has competence, both absolute and relative competence. The absolute competence of the judiciary is the jurisdiction of the judiciary in examining certain types of cases which are absolutely unable to be examined by other court bodies, either in the same judicial environment or in a different judicial environment. In connection with disputes involving sharia banking, until now it is still a matter of debate, which court has the authority to try them. Not to mention that until now there are still decisions of district courts that accept and grant claims which are disputes involving sharia banking. This means that internally the Supreme Court alone, in this case the judges in making decisions are still unable to provide legal certainty regarding absolute competence in adjudicating disputes involving sharia banking